KOMUNIKASI INTERPERSONAL PECANDU GAME ONLINE MOBILE LEGEND PADA MAHASISWA STISIP WIDYAPURI MANDIRI SUKABUMI - Rafli Saputra Rafendi (Jurnalika : Jurnal Ilmu Komunikasi, 2025)
This research is motivated by the existence of a problem that was found during the pre-survey regarding the phenomenon of online game addicts. Namely regarding interpersonal communication on openness, empathy, supportive attitude, positiv attitude and equality. The purpose of this study was to determine the extent of interpersonal communication of online mobile lagend game addicts in STISIP Widyapuri Mandiri Sukabumi students. The theory used refers to Devito's theory (1997: 259) in Suranto Aw (2011: 82-84) with 5 research dimensions namely openness, empathy, supportive attitude, positive attitude, and equality. The approach in this study uses a qualitative approach with descriptive methods. Data collection techniques using interview techniques, observation, and documentation as well as applying triangulation techniques. Then data analysis using data reduction, data presentation, and drawing conclusions. Determining informants was carried out by purposive sampling, as many as 7 (seven) people, namely students. The results of the study show that student interpersonal communication has not gone well. This can be seen from the attitude of openness in interpersonal communication that is good, the attitude of empathy in interpersonal communication is not good, the attitude of supporting interpersonalcommunication is not good, the positive attitude in interpersonal communication is not good, and the attitude of equality in interpersonal communication is not good. The conclusion of this study is that because the indicators for each dimension are not appropriate, Interpersonal Communication of Online Mobile Game Addicts among STISIP Widyapuri Mandiri Sukabumi Students has not been achieved.